Repellency of two monoterpenoids and neem oil against Callosobruchus maculatus (F.) (University Journal of Zoology, Rajshahi University, 2010)
The repellent activity of monoterpenoids viz. eugenol, zimtaldehyde and neem oil againstpulse beetle, Callosobruchus maculatus (F.) was investigated. Responses varied significantly withcompound, dose and exposure time. The tested components showed highest level of repellencyagainst C. maculatus at a dose of 1 μl. Over 80%, Class V, repellency was achieved after 5 to 60min. treatment with the components at a dose of 1 μl. The repellent action of zimtaldehyde showedthe highest repellency (87.41% at 10 min exposure) status against C. maculatus than neem oil andeugenol, while the lowest (79.46%) was recorded for eugenol at 25 min exposure level.Key words: Repellency; eugenol; zimtaldehyde; neem oil; C. maculatusDOI: 10.3329/ujzru.v28i0.5284Univ. j. zool. Rajshahi Univ. Vol. 28, 2010 pp. 41-44